PENGEMBANGAN PANDUAN PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ACCELERATED INSTRUCTION) DALAM MATA PELAJARAN FISIKA KELAS X SMK DENGAN MENGGUNAKAN EDMODO - Rakhma Ayu Maulidah; Dwi Sulisworo (Universitas Halu Oleo, 2021)
This study aims to develop a cooperative learning guide type TAI (Team Accelerated Instruction) in physics class X SMK using Edmodo and validate the guide. This study uses a research and development method with a 4D model (defines, design, develop, and disseminate). The data collection method in this study was obtained through the validation of the module which was analyzed descriptively and quantitatively, which was expressed as a percentage. The results of the validation are as follows; in the module validation that was carried out by the validators after being analyzed, the average result was 79% which indicated that the module was feasible and valid to be tested in the field with revisions